The role of innovative technologies in increasing the level of professional competence of the future physics teacher - Yermekova, Zh.K.; Kozhabekova, E.K.; Sagyndykova, G.E. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
Modern pedagogical science states that the new concept of education of the XXI century is being developed through the prism of improving the culture of the personality of the future teacher, which should include a set of knowledge, skills and, most importantly, the cultural and moral values accumulated by mankind, which are necessary for the formation and development of a competent personality, its professional maturity. The article deals with the problem of training teachers for innovative activities in the context of distance learning. The necessity of this component of professional training of teachers is substantiated, the features of an innovative approach to the organization of the educational process are described, the essence of the innovative orientation of pedagogical activity is revealed. The authors believe that the primary, main, but long–term goal is the formation of a competent personnel potential of teachers of a new formation, justifying the quite obvious: the direct dependence of the quality of the education system on the quality of teachers working in it. Proposed solutions to the problems of training highly qualified, competent physics teachers of a new formation who are able to work in distance learning, create high-quality electronic resources for students on the basis of innovative technologies and who are ready to effectively implement them in the pedagogical system
Болашақ физика мұғалімінің кəсіби құзыреттілік деңгейін көтеруде инновациялық технологиялардың маңыздылығы
Роль инновационных технологий в повышении уровня профессиональной компетентности будущего учителя физики
Keywords: physics teachers; educational process; new formation; innovative technologies; competence; educational program; distance learning; intersubject connections